Physiological, biomechanical, and subjective effects of medio-lateral distance between the feet during pedalling for cyclists of different morphologies - Millour, G.; Duc, S; Puel, F.; Bertucci, W. (Journal of Sports Sciences, 2021)
Improper medio-lateral distance between the feet in cycling can increase the risk of injuries and decrease performance due to hip/knee/ankle misalignment in the frontal plane. The objective of this study was to measure the impact of pedal spacing changes during pedalling on the biomechanical, physiological, and subjective variables of people with different morphologies. Twenty-two cyclists were divided into two groups according to their pelvis width (narrow and wide). They performed four submaximal pedalling tests with different pedal spindle lengths (+20 mm, +40 mm, and +60 mm compared to the pedal spindle lengths of standard road bikes). EMG activity, 3D joint kinematics of the lower limbs, comfort, and perceived exertion were measured during each test. Moreover, gas exchange data were collected to measure gross mechanical efficiency and cycling economy. No significant differences in muscular activity or joint kinematics were observed among the four experimental conditions. However, gross mechanical efficiency, cycling economy, and perceived comfort significantly improved while perceived exertion significantly reduced with the narrowest pedal spacing for the whole population, as well as for the narrow and wide pelvis groups. Therefore, the lowest medio-lateral distance between the feet seems more suitable for comfort and performance improvement, irrespective of the individual`s morphology.